Influence of environmental drivers on spatio-temporal dynamics of satellite-derived chlorophyll a in the Strait of Georgia. (September 2019) - Suchy, Karyn D.; Le Baron, Nicole; Hilborn, Andrea; Perry, R. Ian; Costa, Maycira
Highlights: Phytoplankton in the Strait of Georgia is highly variable over space and time. No single environmental driver can effectively explain variations in phytoplankton. Phytoplankton in the Northern Strait of Georgia is linked to climate indices. Phytoplankton in the Central Strait of Georgia is influenced by localized factors. Abstract: The Strait of Georgia is a dynamic region with substantial spatio-temporal variability at lower trophic levels. This variability, in turn, may directly impact resident and migratory fish populations that are of major economic importance. MODIS-Aqua satellite products were used to provide a comprehensive spatial analysis of phytoplankton dynamics from 2003 to 2016 in the Northern and Central Strait of Georgia (SoG) in order to examine the relationships between environmental drivers and satellite-derived chlorophyll a (Chl a ). Positive SST anomalies predominated between 2003–2006 and 2013–2016, with the strongest anomalies occurring from 2014 to 2016. Strong positive anomalies in Fraser River discharge, coupled with fewer wind events, led to early stratification during spring 2005 and 2015, resulting in moderate to strong anomalies in Chl a concentrations. Chl a in the Northern SoG was most highly correlated with SST and PAR (rs  = 0.41, p < 0.01 and rs  = 0.38, p < 0.01, respectively), whereas Chl a in the Central SoG was most highly correlated with Fraser River discharge (rs  = 0.43, p < 0.01). Annual median Chl a anomalies were tightly coupled with large-scale climate indices (PDO, NPGO, SOI) in the Northern region; however, no such relationships were observed in the Central SoG, suggesting that variability in Chl a in the Central region is more strongly influenced by localized factors. Results from this study provide critical information regarding the key environmental drivers influencing spatio-temporal dynamics of Chl a in the SoG.